MECHANISMS TO ENSURE EFFECTIVENESS OF GERMAN LANGUAGE TEACHING IN HIGHER EDUCATION INSTITUTIONS - Masodikova Zulfiyakhon (Galaxy International Interdisciplinary Research Journal, 2022)
The article describes and analyzes in detail the effective means of using interactive methods of foreign language teaching. This article shows ways to increase the effectiveness of education using pedagogical technologies in German language classes, educational games in the course of the lesson, and ways to achieve active participation of students.